Baseline Modified Glasgow Prognostic Score Associated with Survival in Metastatic Urothelial Carcinoma Treated with Immune Checkpoint Inhibitors. (18th March 2021) - Brown, Jacqueline T.; Liu, Yuan; Shabto, Julie M.; Martini, Dylan J.; Ravindranathan, Deepak; Hitron, Emilie Elise; Russler, Greta Anne; Caulfield, Sarah; Yantorni, Lauren Beth; Joshi, Shreyas S.; Kissick, Haydn; Ogan, Kenneth; et al.
Abstract: Background: The modified Glasgow prognostic score (mGPS), a clinical tool that incorporates albumin and C‐reactive protein, has proven useful in the prognostication of multiple cancers. Several immune checkpoint inhibitors (ICIs) have been approved for the treatment of metastatic urothelial cell carcinoma (mUC), but a prognostic biomarker is needed. We investigated the impact of mGPS on survival outcomes in patients with mUC receiving ICIs. Materials and Methods: We retrospectively reviewed patients with mUC treated with ICIs (programmed cell death protein 1 or programmed cell death ligand 1 inhibitors) at Winship Cancer Institute from 2015 to 2018. Overall survival (OS) and progression‐free survival (PFS) were measured from the start date of ICI until death or clinical or radiographic progression, respectively. mGPS was defined as a summary score with one point given for C‐reactive protein >10 mg/L and/or albumin <3.5 g/dL. Univariate (UVA) and multivariate (MVA) analyses were carried out using Cox proportional hazard model. These outcomes were also assessed by Kaplan‐Meier analysis. Results: A total of 53 patients were included with a median follow‐up 27.1 months. The median age was 70 years, with 84.9% male and 20.8% Black. Baseline mGPS was 0 in 43.4%, 1 in 28.3% and 2 in 28.3%. Increased mGPS at the time of ICI initiation was associated with poorer OS and PFS in UVA, MVA, and Kaplan‐Meier analyses. Conclusion: The mGPS may be a useful prognostic tool in patients with mUC when treatment with ICI is under consideration. These results warrant a larger study for validation. Implications for Practice: The ideal prognostic tool for use in a busy clinical practice is easy‐to‐use, cost‐effective, and capable of accurately predicting clinical outcomes. There is currently no universally accepted risk score in metastatic urothelial cell carcinoma (mUC), particularly in the immunotherapy era. The modified Glasgow prognostic score (mGPS) incorporates albumin and C‐reactive protein and may reflect underlying chronic inflammation, a known risk factor for resistance to immune checkpoint inhibitors (ICIs). This study found that baseline mGPS is associated with survival outcomes in patients with mUC treated with ICIs and may help clinicians to prognosticate for their patients beginning immunotherapy. Abstract : Several immune checkpoint inhibitors have been approved for the treatment of metastatic urothelial cell carcinoma, but a prognostic biomarker is needed. This article reports on the effect of the Glasgow prognostic score on survival outcomes in patients with metastatic urothelial cell carcinoma receiving immune checkpoint inhibitor therapy.